Strategic cost management - Cabrera, Ma. Elenita B.; Cabrera, Gilbert Anthony B.; Cabrera, Bernadette Ann B. (Manila : GIC Enterprises, 2021)
The central focus of this 2021 Edition of Strategic Cost Management is how management accounting helps managers better plan, control and decide for their companies. This book can be used immediately after the student has had an introductory course in Cost Accounting and Control.
I. Introduction to strategic cost management -- II. Strategic cost management concepts and techniques for planning and control -- III. Cost management concepts and tools for decision making -- IV. Cost management concepts and techniques for control and strategic performance measurement.
Includes bibliographical references.
Keywords: COST ACCOUNTING; MANEGERIAL ACCOUNTING